2020
DOI: 10.3389/fpsyg.2020.00231
|View full text |Cite|
|
Sign up to set email alerts
|

Expressive Brand Relationship, Brand Love, and Brand Loyalty for Tablet PCs: Building a Sustainable Brand

Abstract: This study was conducted from the strategic marketing perspective to test the impact of brand relationship types on brand loyalty. We also test three path effects of brand love and brand trust. Data were collected from three metropolitan customers who use tablet PCs. We obtained 383 valid samples, giving a valid response rate of 89%. Data analysis was performed with SmartPLS2.0 and SPSS 23.0 to test the proposed model. The results indicate that an expressive brand relationship significantly predicts brand trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 66 publications
7
48
0
5
Order By: Relevance
“…Their study has confirmed the positive relationships between brand experience and brand love ( β = 0.30), and brand love and brand loyalty ( β = 0.70) (Bıçakcıoğlu et al, 2018). Our data concurred with existing research (Zhang et al, 2020) and reported similarly high coefficients between brand love and loyalty, but we further explored if the relationships remain the same in attitudinal and behavioural brand loyalty by examining the multidimensionality of brand love (Ong et al, 2018). Brand love was found in our study to influence consumers’ brand preference and future purchase intention (i.e., behavioural brand loyalty) more than their intention to recommend to others, despite its premium price (i.e., attitudinal brand loyalty) (Huang, 2017; Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Their study has confirmed the positive relationships between brand experience and brand love ( β = 0.30), and brand love and brand loyalty ( β = 0.70) (Bıçakcıoğlu et al, 2018). Our data concurred with existing research (Zhang et al, 2020) and reported similarly high coefficients between brand love and loyalty, but we further explored if the relationships remain the same in attitudinal and behavioural brand loyalty by examining the multidimensionality of brand love (Ong et al, 2018). Brand love was found in our study to influence consumers’ brand preference and future purchase intention (i.e., behavioural brand loyalty) more than their intention to recommend to others, despite its premium price (i.e., attitudinal brand loyalty) (Huang, 2017; Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Our data concurred with existing research (Zhang et al, 2020) and reported similarly high coefficients between brand love and loyalty, but we further explored if the relationships remain the same in attitudinal and behavioural brand loyalty by examining the multidimensionality of brand love (Ong et al, 2018). Brand love was found in our study to influence consumers’ brand preference and future purchase intention (i.e., behavioural brand loyalty) more than their intention to recommend to others, despite its premium price (i.e., attitudinal brand loyalty) (Huang, 2017; Zhang et al, 2020). Because brand love is an important determinant of brand management strategies (Bıçakcıoğlu et al, 2018), our findings also help understand ad-induced brand experience and its effects on creating brand love and brand loyalty to foster strong brand equity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Earlier authors provided the scale items of the variables of the study. The indicator items of credibility were from Erdem and Swait (2004), image from Yoo, Donthu and Lee (2000) and Gil, Andrés and Salinas (2007), satisfaction from He, Li and Harris (2012) and Delgado-Ballester and Munuera-Alemán (2005) and behavioural intentions from Zeithaml et al (1996), Zhang et al (2020) and Netemeyer et al (2004). The research assistants distributed the questionnaires to the customers who were leaving the herbal stores after purchases using a systematic sampling technique.…”
Section: Scale Items Development and Data Collection Procedurementioning
confidence: 99%